Correlation between multifunctional properties of lead free Iron doped BCT perovskite ceramics. Issue 11 (1st August 2020) - Redhu, Preeti; Punia, Rajesh; Hooda, Ashima; Malik, B.P.; Sharma, Geeta; Sharma, Preeti
Abstract: Present study investigates the effect of Fe doping on structural, microstructural, dielectric, ferroelectric, piezoelectric and magnetic properties of Barium calcium titanate (BCT) ceramics synthesized by solid state reaction route. The polycrystalline tetragonal structure of prepared ceramics was confirmed from XRD study. Analysis done using Rietveld refinement reveals reduction in lattice parameters as well as unit cell volume on substitution of Fe 3+ ions in BCT lattice. Occurrence of four distinct Raman bands viz . 297 cm −1 -302 cm −1, 473 cm −1 -475 cm −1, 516 cm −1 -524 cm −1 and 729 cm −1 -733 cm −1 in Raman spectroscopic studies confirms the tetragonal phase of prepared ceramic compositions which are in accordance with XRD study. The Scanning Electron Microscopy analysis revealed polyhedral shaped grains whose average grain size decreased with increase in Fe content (x) in BCT ceramics. A diffused frequency independent phase transition was observed in temperature dependent dielectric measurements. Dielectric properties improved significantly, with shifting of transition temperature, Tc close to room temperature with Fe doping. These studiessuggest applications of these ceramics in the development of environment friendly dielectric materials meeting X7R MLCCs specifications. The ferroelectric and piezoelectric properties of these ceramic compositions were found to decrease with increase in Fe concentration. Feeble room temperature ferromagnetism was observed for composition x = 0.020.